O Grupo Escolar Bueno Brandão como expressão republicana no município de Uberabinha, Mg 1911-1930 - Santos, Mileide Mateus dos (2019)
This study deals with the origins of Júlio Bueno Brandão Public School operations in the city of São Pedro de Uberabinha. The study aimed to understand how Republican ideas were expressed in Uberabinha through this school and what it required from the local society; that is, it sought to place the school Júlio Bueno Brandão in public education reforming movement in order to understand financing through the school fund (circumstances of its creation and associated actions) as well as its daily functioning based on professional and pedagogical relationships. Constructing such an understanding required contextualizing childhood in this primary school according to a theoretical-methodological and dialectical framework that articulates the local context with the general in the light of sources (notebooks of activities of students, meetings minutes, newspapers, etc.). Documents and bibliography was worked dialectically, in order to encompass childhood in the historical process of the public school in Uberabinha in its first five years of life. The research covered 1911–1930 period. Results indicate, among other findings, concern of the school as to maintain its operations as well as to control student behavior and school attendance. Among mechanisms applied to this end, the creation and actions of a school funding helped to co-opt professors and students in the process of consolidating the public school locally: by subjecting themselves to frequency and behavior standards as well going to the streets to exposing the public education material conditions to sensitizing society to the point of making people help to keep the school group operating and able to fulfill expectations of schooling Republicans raised in population. Keywords: society; public school; school fund; financial aid